Modelling of earthquake-induced pounding between adjacent structures with a non-smooth contact dynamics method. (15th August 2021) - Langlade, T.; Bertrand, D.; Grange, S.; Candia, G.; de la Llera, J.C.
Highlights: A complementarity method imposes the velocities at the nodes of colliding structures. The non-smooth contact dynamics method is efficient in the building pounding context. The coefficient of restitution is assessed to 0.6 for slab-slab pounding. A numerical versus experimental comparison of pounding structures gives good matching. Abstract: This article presents the kinematic analysis of two adjacent structures with pounding using the framework of finite element dynamic analysis and a non-smooth contact dynamics (NSCD) method for treating contact-impact. The latter consists of a Moreau-Jean implicit integration scheme that uses Moreau's sweeping process and Newton's impact law. Test cases are carried out to prove the efficiency of the implementation and accuracy of the results relative to the widely used penalty method (PM). Furthermore, finite element simulations are compared with shaking table results of two structures susceptible to pounding. Models are steel frames 2.5 m to 5 m high, 3 m in span, have reinforced-concrete slabs, and distant 0 to 5 cm. Floor displacements, number and time of occurrence of impacts, as well as shape of the response spectra are in good agreement with experimental observations. Moreover, using the building pounding frame and the NSCD method, an estimation of a constant value for the coefficient of restitution was carried out. It is concluded that the NSCD method is a very numerically efficient tool in terms of reduction of CPU time and description of the impact physics. Consequently, this approach is amenable for fragility analysis of the dynamic response of structures involving a contact-impact phenomenon.